Reflexivity and Relational Spaces: Experiences of Conducting a Narrative Inquiry Study With Emerging Adult Women Living With Chronic Pain - Jenise Finlay; Aniela dela Cruz (SAGE Publishing, 2023)
Clandinin and Connelly's narrative inquiry methodology was used to understand the lived and told stories of two emerging adult women (aged 18-29) living with chronic pain. The aim of this paper is to share the experiences of the first author-a graduate student and novice researcher-of creating relational spaces with emerging adult women living with chronic pain, and the experience of co-creating knowledge through the methodological lens of narrative inquiry. There are 12 qualitative touchstones that narrative inquirers attend to when using narrative inquiry, and we present the experiences of a novice narrative inquirer in relation to selected touchstones. Narrative inquiry can greatly contribute to nursing knowledge, and implications for nursing practice and research are discussed.